Extraction of chitin from chitosan from exoskeleton of shrimp for application in the pharmaceutical industry - Puvvada, Yateendra Shanmukha; Vankayalapati, Saikishore; Sukhavasi, Sudheshnababu (International Current Pharmaceutical Journal, 2012)
Chitosan is an amino polysaccharide prepared by processing shrimp waste (shell) which involves partial deacetylation of chitin. Chitosan, a versatile natural polysaccharide, the second most abundant natural polymer. Many biochemists have found that chitosan as biocompatible, biodegradable and non toxic which made wide applicability in conventional pharmaceutics as a potential formulation excipient. In this research mainly the focused on the synthesis of chitosan which is suitable for the pharmaceutical industry especially in the designing delayed and controlled drug delivery systems. The main study focused on preparation low molecular weight of the chitosan suitable for pharmaceutical industry. The crude chitin was collected from exoskeleton of Triopslongicaudatus and Triopscancriformis specimens which are then processed to obtain chitosan. The chitosan yield was found to be 35.49% and it was analyzed for its physiochemical parameters. DOI: http://dx.doi.org/10.3329/icpj.v1i9.11616 International Current Pharmaceutical Journal 2012, 1(9): 258-263